Pelaksanaan Pekerjaan Perkerasan Lentur pada Proyek Pelebaran Jalan di daerah Branjang-Lerep, Kabupaten Semarang - Ahmat Sofyan; Agung Hari Wibowo (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2021)
This study analyzes the implementation of a widening project on a road section in the Branjang-Lerep area, Semarang Regency, Central Java, with a focus on the flexible pavement sub-layer. This project was carried out by a contractor under the supervision of the project implementer. The scope of work included earthworks, channels and culverts, granular pavement, and flexible pavement. The research method used field observations, literature studies, and interviews. The observations revealed significant challenges related to extreme geographical conditions (slopes, sharp bends), weather, and social aspects (heavy traffic). Although material quality control demonstrated adequate results, the implementation of Occupational Health and Safety (OHS) still needed improvement. Implemented solutions included adapting the asphalting work schedule, using heavy equipment adapted to the terrain, and partial traffic management to maintain the smooth flow of community activities. This article provides a comprehensive overview of the challenges and adaptation strategies in road infrastructure projects in areas with difficult topography and heavy traffic.